Implementasi Praktik Lintas Bidang pada Materi Berpikir Komputasi untuk Tingkat Sekolah Menengah Pertama dengan Mendayagunakan Alat Bantu Praktik - Bambang Pudjoatmodjo; Rickman Roedavan; Desy Puspa Rahayu (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
The development of the digital era has made the mastery of computational thinking a key component in informatics education, particularly at the middle school level. This community service activity aims to enable middle school informatics teachers in Bandung Regency to integrate computational thinking into the Merdeka Curriculum. The assistance provided to teachers encompasses not only the technical aspects of teaching informatics but also a deep understanding of computational thinking as a crucial tool for developing students' analytical, creative, and problem-solving abilities. Key aspects emphasized include algorithms, data modeling, abstraction, and automation, as well as their practical applications in everyday problem-solving and cross-disciplinary contexts. This activity promotes a paradigm shift in the teaching of informatics from a technical understanding of computers to an approach that combines theoretical instruction with practical application, aiming to prepare students for the challenges of a digital world. In its evaluation, this activity was deemed successful as participants' post-test scores ranged from 80 to 100. Consequently, it is expected that the teachers